Cello Playing Technique in the Presentation of Sonata E Minor RV Op.14 by Antonio Vivaldi - Manalu, Kartini R.M; Nainggolan, David B.; Gulo, Kevin Marchell (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research to describe the playing technique and presentation of Sonata E Minor RV 40 Op 14 by Antonio Vivaldi on cello instrument. The focus of the research is on legato and trill techniques used in this piece,including the challenges faced during recital preparation and the solutions found. The legato technique provides a smooth flow of notes, which trills add dynamics to the melody.The main difficulties included intonation, dynamics, and bow control. The presentation of this work is done in solo cello format with piano accompaniment. This research is expected to be a reference for cellists in learning similar works.